The Importance of Ethics in Research in The Field: Systematic Literature Review - Hidayat, Moh. Nurul; Mukhlis, Imam (Business and Investment Review, 2024)
Field research is research that has direct contact with sources. conflict of interest of researchers involved in a study. The purpose of this research is to determine the importance of ethics in research. The method used in this research uses PRISMA where the steps in searching for data consist of identification, screening, eligibility and inclusion. , with data sources Google Scholar, ScienceDirect, and the Diva portal. Researchers need procedures and ethics that can monitor and ensure they remain in the correct and safe areas. What is no less important is critical and reflexive thinking and actions during research. policymakers should revisit guidance on research ethical vulnerabilities, and we suggest that a stakeholder engagement process would greatly aid that work